The Public Value of e-Government Applications in Jordan: A Qualitative Study Using Artificial Intelligence Tools - Shteiwi, Musa Mufdi; Mdanat, Metri Fayez; Alhur, Mohammad Salem (Jordan Journal of Social Sciences, 2024)
The utilization of the public value approach has emerged as a novel methodology for evaluating the efficacy of public services on a global scale. A comprehensive examination of existing literature reveals a scarcity of empirical studies that assess e-government applications in terms of public value, particularly within the context of Jordan. Hence, the present investigation aims to assess e-government services in terms of their users' perceived value. In order to accomplish this, the present study has established the following objectives: Evaluation of e-government applications from the perspective of their users based on public value dimensions Understanding the prevalent preference for these applications Determining the strengths and weaknesses of e-government apps from the user's perspective. Formulating recommendations based on this study's findings In order to accomplish the objectives, the study employed a methodology comprising of four different stages: (1) extracting data from Google and Apple stores; (2) data preprocessing; (3) designing ground truth data; (4) training machine learning models; (5) analyzing the sentiment polarity of those applications; and (6) extracting the main themes by thematic analysis. The study revealed that the majority of evaluations were positive, with the exception of apps in the social care sector, which received negative reviews. This indicates that the majority of users found e-government applications to be helpful. However, the results suggest that e-government applications have damaged the trust between them and their users, as evidenced by the negative comments made by their users. In addition, there is a disparity in the level of electronic services provided by e-government applications to citizens. E-government applications promote equality and public interest technology by providing services fairly and equitably to all users, as well as by establishing a balance between individual benefit and public interest, as provided by security applications. The study recommended the adoption of a technological code of conduct and the development of applications that adhere to international design standards, such as usability and aesthetics.